Sun Nepal Life Insurance Company: Customer Satisfaction to Its Products - Bhattarai, Dilli Bahadur (Kanakai Journal, 2022)
This study explores customer satisfaction towards the products and services of the Sun Nepal Life Insurance Company Ltd. Customer satisfaction with company’s products and services is often seen as the key to a company’s success and long-term competitiveness. In other words, customer satisfaction is defined as a measurement that determines how happy. They are with the company’s product, services and capabilities. Customer satisfaction information, including surveys and ratings, can help a company determine how to improve the best of their products and services and identify the area which needs improvement in order to maintain or increase their quality of services and membership base. This research tries to systematically review significance of life insurance in modern competitive and risky human life due to risky society, busy scheduled, unhygienic life style etc. The study uses descriptive and percentage techniques for data analysis after the collection of data entry is checked. The primary data was collected through survey. About 100 questionnaires were distributed in Jhapa district, out of which 87 questionnaires were received back. This study is very helpful to see the effect of customer satisfaction and attitude towards SNLIC.